Structural Determinants of Regional Poverty in West Nusa Tenggara - Loka, Intania Puspita; Margaret, Silvia (Signifikan: Jurnal Ilmu Ekonomi, 2026)
Research Originality: This study contributes to the existing literature by examining the structural determinants of regional poverty at the regency and municipal levels in West Nusa Tenggara Province using the most recent post-pandemic panel dataset. Research Objectives: This study aims to analyze the effects of minimum wages, open unemployment rates, income inequality, and educational attainment on poverty rates in West Nusa Tenggara Province. Research Methods: The study uses panel data spanning 2018–2024 and covers 10 regencies and municipalities in West Nusa Tenggara Province. The Fixed Effects Model (FEM), selected based on the Chow and Hausman specification tests, is employed to estimate the relationship between poverty rates and the explanatory variables. Empirical Results: The results indicate that the minimum wage has a negative, statistically significant effect on poverty rates, whereas income inequality has a positive effect. In contrast, the open unemployment rate and educational attainment do not demonstrate statistically significant effects on poverty. Implications: These findings suggest that poverty alleviation strategies should prioritize strengthening wage protection frameworks and mitigating income inequality to foster inclusive and sustainable regional development. JEL Classification: I32, O15, J31, R11